mGluR1 signaling is necessary for strengthening winner climbing fiber inputs in the developing mouse cerebellum - Miwako Yamasaki; Taisuke Miyazaki; Kouichi Hashimoto; Norio Takei; Atsu Aiba; Masanobu Kano; Masahiko Watanabe (Proceedings of the National Academy of Sciences, 2026)
Functional neural circuits are sculpted by strengthening frequently used synapses and removing unnecessary connections. At birth, cerebellar Purkinje cells receive inputs with similar synaptic strengths from multiple climbing fibers (CFs). During postnatal development, a single “winner” CF is selectively strengthened and expands its dendritic innervation territory, while somatic “loser” synapses are eliminated. Here, we report that deleting metabotropic glutamate receptor 1 (mGluR1) or protein kinase Cγ (PKCγ) in mice disrupts this selective strengthening and territory expansion of “winner” CFs during early development. This impairment leads to weaker synaptic transmission and diminished dendritic innervation territory of “winner” CFs at later stages. Notably, “winner” CF synapses in these mutants exhibit impaired long-term potentiation, reduced AMPA receptor expression, and simpler postsynaptic organizations. These findings reveal a previously unappreciated role for mGluR1–PKCγ signaling, besides its established role in eliminating “loser” CFs, in promoting the functional and structural maturation of “winner” CF synapses.